VUV photochemistry simulation of planetary upper atmosphere using synchrotron radiation - Carrasco, Nathalie (Journal of synchrotron radiation, 2013)
The coupling of a gas reactor, named APSIS, with a vacuum-ultraviolet (VUV) beamline at the SOLEIL synchrotron radiation facility, for a photochemistry study of gas mixtures, is reported. The reactor may be irradiated windowless with gas pressures up to hundreds of millibar, and thus allows the effect of energetic photons below 100 nm wavelength to be studied on possibly dense media. This set-up is perfectly suited to atmospheric photochemistry investigations, as illustrated by a preliminary report of a simulation of the upper atmospheric photochemistry of Titan, the largest satellite of Saturn. Titan's atmosphere is mainly composed of molecular nitrogen and methane. Solar VUV irradiation with wavelengths no longer than 100 nm on the top of the atmosphere enables the dissociation and ionization of nitrogen, involving a nitrogen chemistry specific to nitrogen-rich upper atmospheres